The Settlement of Disputes over Syariah Banking in the Religious Court - Bambang Utoyo; Budi Santosa (The Southeast Asia Law Journal, 2016)
Law No. 7/1992, the law No. 10 /1998 and the law No. 23/ 1990 actually has become a strong legal basis for holding syariah banks in Indonesia, although there are still some things that still need to be perfected, including the need for arranging and enhancements to the terms of the legislation regarding be syariah banks separately so that when there was a dispute in this relation with syariah banking can be resolved by reference to the applicable law. At the beginning which become the problems of the law for the settlement of disputes of syariah banking is about to be brought where the solution, because the Court did not use the syariah as the legal basis for the settlement of the matter, while under the jurisdiction of the Court when it according to Act No. 7 1989 only limited to judge things marriage, inheritance, guardianship, grants, endowments and shadaqoh. So then to anticipate emergency condition then established Convenient Arbitration Indonesia (BAMUI) established jointly by the office of the General Attorney ofthe Republic of Indonesia and the MUI.Keywords: The settlement of Disputes, Convenient Arbitration Indonesia